Chemistry of naturally layered manganites - Battle, P; Kasmir, N; Millburn, J; Rosseinsky, M; Patel, RT; Spring, L; Vente, J; Blundell, S; Hayes, W; Klehe, A; Mihut, A; Singleton, J (1998)
Experiments on three double-layer (n=2) Ruddlesden-Popper (RP) systems are reported. Doping Sr1.8La1.2Mn2O7 (T-c = 126 K) with Nd to form Sr1.8La1.2-xNdxMn2O7 leads to a reduction in Curie temperature for low doping levels (x = 0.2), and to behavior reminiscent of Sr1.8Nd1.2Mn2O7 for x greater than or equal to 0.7. This suggests that it may be possible to control the temperature of maximum magnetoresistance chemically in these phases. The application of pressure (0 < P/GPa less than or equal to 1.8) is shown to modify the magnetotransport properties of Sr2NdMn2O7 to resemble those of Sr1.9Nd1.1Mn2O7. The changes can be explained by considering the relative strength of ferromagnetic and antiferromagnetic interactions within the material. Finally, the need for careful phase analysis of n = 2 RP materials is demonstrated by the misleading magnetization data recorded for a sample of Sr1.8Sm1.2Mn2O7 containing similar to 2.8% of an n = infinity perovskite phase. (C) 1998 American Institute of Physics. [S0021-8979(98)20911-X].